Examining and Improving Provider Adherence to the Primary Care Mental Health Integration Model. Issue 9 (3rd July 2020) - Possis, Elizabeth; Skroch, Beret; Hintz, Samuel; Bronars, Carrie; Mallen, Michael; Crowl, Haley; Moore, Kelly; Bemmels, Heather; Olson, Douglas
Abstract: Introduction: The Veterans Health Administration (VHA) is a national leader in integrated care, known in the VHA as the Primary Care Mental Health Integration (PCMHI) model. This model is associated with improved quality of services and same-day access for veterans. There has been some recent development of PCMHI/integrated care competencies within VHA and across the nation. To fully implement these competencies, however, PCMHI providers must not only be trained, but their adherence to the PCMHI model must also be assessed. While there have been recent advances, there has been little research that has examined the adherence of PCMHI providers to the model or methods to improve adherence. Materials and Methods: The present study sought to examine and improve the clinical practice of a team of eight PCMHI providers to make practice more adherent to the PCMHI model. This study was conducted at a large Midwestern VA Medical Center using interventions based in assessment, feedback, and training—measured at three points in time. The Primary Care Behavioral Health Provider Adherence Questionnaire (PPAQ; Beehler GP, Funderburk JS, Possemato K, et al.: Psychometric assessment of the primary care behavioral health provider adherence questionnaire (PPAQ). Transl Behav Med 2013; 3: 379–91.) was used to assess provider adherence and the PPAQ toolkit was used to provide tailored recommendations for improving provider practice. In addition, the VHA "Foundations Manual" and Functional Tool outlined essential behavioral targets that are consistent with the PCMHI model and the "essential provider behaviors" from the PPAQ. A combination of individual and group interventions was presented and adherence, pre and post, was assessed with the PPAQ and with evaluation of clinical practice data. Results: Results indicated that the behavior of PCMHI providers changed over time, with providers exhibiting more PCMHI consistent behaviors and fewer inconsistent behaviors. Adherence to the PCMHI model increased. Conclusion: Providing assessment, feedback, and training in the PCMHI model changed the clinical practice of PCMHI providers and resulted in improved adherence. Clinical and research implications are discussed.